Comparison of the analgesic effects of oxycodone vs. sufentanil on postoperative pain after laparoscopic gallbladder-preserving cholecystolithotomy: a prospective randomized controlled trial - Wang, Ye; Wu, Meng; Zhao, Lin; Yan, Xiaojian; Zhao, Lei (Frontiers in Surgery, 2024)
Background We aimed to compare the anesthesia induction effects of oxycodone and sufentanil on postoperative pain in patients undergoing laparoscopic gallbladder-preserving cholecystolithotomy, as well as changes in serum levels of inflammatory factors (TNF-α, IL-6, and IL-10) in the perioperative period. Methods Sixty patients who underwent laparoscopic gallbladder-preserving cholecystolithotomy were evenly divided into oxycodone (O) and sufentanil (S) groups. In groups O and S, oxycodone (0.3 mg/kg) and sufentanil (0.3 ug/kg) were administered, respectively, followed by propofol (2 mg/kg) and rocuronium (0.6 mg/kg). In both groups, the intraoperative electroencephalography double-frequency index was used to guide the use of sedative and analgesic drugs, assessing the follow-up analgesic effect (VAS), degree of sedation (Ramsey), and postoperative complications at seven different time points (0, 0.5, 2, 4, 6, 8, and 24 h postoperatively). Results Compared with the S group, patients in the O group exhibited lower VAS scores within 24 h postoperatively (P < 0.001), but there was no statistical difference between wound and shoulder pain scores (P > 0.05). Regarding postoperative awakening and extubation duration, O group patients experienced shorter times and better remedial analgesia (P < 0.05). In terms of the degree of sedation, the Ramsay score decreased at 0 h postoperatively compared with the S group (P < 0.001). Conclusion Compared with sufentanil, oxycodone anesthesia induced better postoperative analgesia and less inflammatory responses in patients undergoing laparoscopic gallbladder-preserving cholecystolithotomy. Clinical Trial Registration This study has been approved by the Ethics Committee of Peking University Shougang Hospital, with ethical approval (No. IRBK-2020-009), and has completed registration in the Chinese Clinical Trials Register (http://www.chictr.org.cn/) (ChiCTR2000031230).